Locally adaptive temperature response of vegetative growth in Arabidopsis thaliana - Clauw, Pieter; Kerdaffrec, Envel; Gunis, Joanna; Reichardt-Gomez, Ilka; Nizhynska, Viktoria; Koemeda, Stefanie; Jez, Jakub; Nordborg, Magnus (eLife, 2022)
We investigated early vegetative growth of natural Arabidopsis thaliana accessions in cold, nonfreezing temperatures, similar to temperatures these plants naturally encounter in fall at northern latitudes. We found that accessions from northern latitudes produced larger seedlings than accessions from southern latitudes, partly as a result of larger seed size. However, their subsequent vegetative growth when exposed to colder temperatures was slower. The difference was too large to be explained by random population differentiation, and is thus suggestive of local adaptation, a notion that is further supported by substantial transcriptome and metabolome changes in northern accessions. We hypothesize that the reduced growth of northern accessions is an adaptive response and a consequence of reallocating resources toward cold acclimation and winter survival.
Keywords: cold; winter; adaptation; growth